Corporate Disclosure Readability and Investor Decision-Making: Experimental Evidence from Financial and ESG Information - Widyatama, Arif (University Merdeka Malang, 2026)
The readability of corporate disclosure plays a crucial role in shaping investors’ ability to process information and make investment decisions. However, experimental evidence on how the readability of both financial and non-financial disclosures influences investor behavior remains limited, particularly in emerging markets. This study examines the effect of corporate disclosure readability on investor decision-making by focusing on financial and environmental, social, and governance (ESG) information. Using a 2 × 2 between-subjects experimental design, the study manipulates the readability of financial and ESG disclosures presented to participants. The experiment involves 58 accounting students with prior knowledge of investment and portfolio management, acting as surrogate investors. The results indicate that disclosures with higher readability significantly increase investors’ willingness to invest compared with disclosures that are difficult to read. The findings suggest that the clarity of both financial and ESG information enhances information processing and influences investment judgments. This study contributes to the literature on corporate disclosure readability and provides implications for firms and regulators in improving the accessibility of corporate reporting.